A Miniaturized Band-Reject Filter Using Metamaterial Structures on Silicon Substrate for X-Band Application. Issue 3 (4th May 2021) - Pradhan, Buddhadev; Gupta, Bhaskar
ABSTRACT: This paper presents a miniature-size band-reject filter on a Coplanar Waveguide (CPW) transmission line using series connected complementary split ring resonators (CSRRs) and series capacitive gaps for X-band applications. The band-reject filter has highly miniaturized dimensions and is capable of solving almost all the basic limitations to which the conventional band-reject filters are mostly susceptible. The series connected CSRRs are etched on the signal planes of the CPW transmission line on silicon substrate enabling CMOS compatibility with planar IC technology. It is a concept resulting in higher bandwidth, low insertion loss of 0.5 dB with high rejection of 40 dB in the stop bands better than similar designs. The optimized design of the proposed device is performed using the parametric study of filter characteristics. The proposed devices RF analysis and circuit model are simulated using Ansoft High-Frequency Structural Simulator (HFSS) v13 ® and Agilent Advanced Design System (ADS) 2009. Measured results are in good agreement with their simulated counterparts and the measured performance is encouraging in all respects.